1919-1920 the Manila Times and Manuel L. Quezon : a historical case study on media ownership and politics - Dantes, Hans Joshua Villas (2012)
"This thesis delves into the interplay between politics and media ownership by filling the gap in the history of one of the oldest newspapers in the Philippines; The Manila Times. The period from 1919 to 1920 was very eventful and crucial for Philippine history as a whole, and specifically for the history of journalism in the Philippines. with the second senatorial elections, the first Independence Mission, the newspaper strike of August 1920, among others. The then-Senate President Manuel Quezon was a major stockholder in the Times Company. Published journalism histories differ as to the images and leanings of the Times during the period. The researchers resolved this issue through the analysis of the paper's issues from 1919-20. This particular case proved contrary to the expectations of theories and common-sense axioms, as Quezon, a newspaper owner directly engaged in the day to day politics of period, was unable to exhibit a dominant influence on the newspaper production process - the American editors and the Filipino rank and file - would vie for the production of images and leanings of the Times as shown in its frontpage articles and editorials."